Unlocking user-driven innovation and sustainable competitive advantage through partnership: An open innovation perspective - Septian Wahyudi; Moris Adidi Yogia; Muhammad Faisal Amrillah (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2023)
This study addresses a research gap in the impact of partnerships on marketing performance in B2B digital start-ups in Indonesia. Although partnerships have been extensively studied from an innovation theory perspective, there still needs to be more research on how combining the advantages of the two, technology and partnerships, can increase the impact of innovation, such as user-driven innovation. The study proposes to explore user-driven innovation as a mediating variable from the perspective of open innovation theory, which can facilitate the relationship between partnerships and marketing performance in B2B digital start-ups in Indonesia. Structural Equation Modeling tests four hypotheses and uses a sample of 262 digital start-ups on Java Island-Indonesia. The result demonstrates two strategic pathways to enhance marketing performance, user-driver innovation and sustainable competitive advantage. This study introduces the role of user-driven innovation in enhancing marketing performance.
Keywords: M13; M31; 330; User-driven Innovation; Partnership; Open Innovation; Sustainable competitive advantage; Start-up performance